The Impact of Interventional Weight Loss on Bone Marrow Adipose Tissue in People Living with Obesity and Its Connection to Bone Metabolism - Tencerova, Michaela; Duque, Gustavo; Beekman, Kerensa M; Corsi, Alessandro; Geurts, Jeroen; Bisschop, Peter H; Paccou, Julien (Nutrients, 2023)
This review focuses on providing physicians with insights into the complex relationship between bone marrow adipose tissue (BMAT) and bone health, in the context of weight loss through caloric restriction or metabolic and bariatric surgery (MBS), in people living with obesity (PwO). We summarize the complex relationship between BMAT and bone health, provide an overview of noninvasive imaging techniques to quantify human BMAT, and discuss clinical studies measuring BMAT in PwO before and after weight loss. The relationship between BMAT and bone is subject to variations based on factors such as age, sex, menopausal status, skeletal sites, nutritional status, and metabolic conditions. The Bone Marrow Adiposity Society (BMAS) recommends standardizing imaging protocols to increase comparability across studies and sites, they have identified both water-fat imaging (WFI) and spectroscopy (1H-MRS) as accepted standards for in vivo quantification of BMAT. Clinical studies measuring BMAT in PwO are limited and have shown contradictory results. However, BMAT tends to be higher in patients with the highest visceral adiposity, and inverse associations between BMAT and bone mineral density (BMD) have been consistently found in PwO. Furthermore, BMAT levels tend to decrease after caloric restriction-induced weight loss. Although weight loss was associated with overall fat loss, a reduction in BMAT did not always follow the changes in fat volume in other tissues. The effects of MBS on BMAT are not consistent among the studies, which is at least partly related to the differences in the study population, skeletal site, and duration of the follow-up. Overall, gastric bypass appears to decrease BMAT, particularly in patients with diabetes and postmenopausal women, whereas sleeve gastrectomy appears to increase BMAT. More research is necessary to evaluate changes in BMAT and its connection to bone metabolism, either in PwO or in cases of weight loss through caloric restriction or MBS, to better understand the role of BMAT in this context and determine the local or systemic factors involved.
Keywords: obezita; tuková tkáň; hmotnostní úbytek; Humans; Bone Marrow; fractures; clinical trials; Female; lidé; weight loss; osteoporosis; ženské pohlaví; Bone Density; kostní dřeň; bone mineral density; kostní denzita; imaging; Obesity; bone marrow adipose tissue; metabolic and bariatric surgery; obesity; Adipose Tissue; Weight Loss